Identification of DDX39A as a Potential Biomarker for Unfavorable Neuroblastoma Using a Proteomic Approach. Issue 2 (15th October 2015) - Otake, Kohei; Uchida, Keiichi; Ide, Shozo; Kobayashi, Yuhko; Kobayashi, Issei; Kusunoki, Masato
Abstract : Background: Malignant potential in unfavorable neuroblastoma (NB) is dependent on an undifferentiated status. The aim of this study was to identify a novel biomarker associated with the undifferentiated status of NB in vitro and to evaluate its prognostic implication. Procedure: Shotgun proteomic analysis was performed in undifferentiated and all trans ‐retinoic acid induced differentiated NB cells in vitro . An identified protein was verified by multiple reaction monitoring (MRM) and evaluated by Western blot analysis. Immunohistochemistry (IHC) was used to examine the expression of the identified protein in 33 primary NB tissues. Results: Twelve proteins, including ATP‐dependent RNA helicase (DDX39A), were only detected in undifferentiated NB cells. A peptide of DDX39A was detected at a significantly higher level in undifferentiated IMR‐32 ( P = 0.002) and LA‐N‐1 ( P < 0.001) cells by MRM. Western blot analysis revealed that DDX39A expression was significantly higher in undifferentiated IMR‐32 ( P = 0.02) and LA‐N‐1 ( P = 0.025) cells. IHC demonstrated that DDX39A was highly expressed in the primary tumor tissues of patients with poor prognosis, and univariate and multivariate survival analyses showed that DDX39A expression could be an independent unfavorable prognostic factor ( P = 0.027). Conclusions: DDX39A is a potential biomarker for unfavorable NB using a proteomic approach. Evaluation of DDX39A protein expression in NB tumor tissues may provide complementary prognostic information for further subclassification of these tumors.